Finding purpose: United States strategic military organizations from 1882-1947 - Moseman, Scott Alan (Kansas State University, 2021)
United States strategic military intelligence organizations have had to adapt to several external and internal factors in finding their raison d’etre. Military intelligence reflects the society it serves as seen in the manner it handled intelligence used by military commanders and policymakers. This subject provides insight to the thought processes of the American government and citizens for which military intelligence professionals worked. The Office of Naval Intelligence’s and Military Intelligence Division’s search for purpose is directly influenced by the trends occurring around them in each era of the period. Historians can observe these principles in American history through a study of these organizations. But there is a relatively small and incomplete historiography of strategic military intelligence organizations stretching from their infancy to the beginning of the Cold War. Much of the scholarship fails to account for how they relate to American society. What were the missions of U.S. strategic military intelligence between 1882 and 1947? From 1882 to 1947, strategic military intelligence organizations struggled to define their missions; the American public, government and military leaders, and intelligence professionals had competing ideas of what strategic military intelligence should be and do. By the time of the post-World War II creation of the modern national security establishment, these actors had learned the place for the armed forces’ own intelligence offices was often in operational intelligence, as part of a broad national intelligence community.
Keywords: Military intelligence; Strategic intelligence; Naval intelligence; Army intelligence; Office of Naval Intelligence; Marine Corps intelligence